(untitled) - Mintzberg, Henry (Englewood Cliffs, N.J., 1991)
Contents provide the reader with a richness of theory, a richness of practice, and a strong basis for linkage between the two.
Keywords: Strategic planning,Lập kế hoạch chiến lược; Case studies,Nghiên cứu trường hợp